Longitudinal and concurrent relationships between caregiver–child behaviours in the vaccination context and preschool attachment. Issue 3 (March 2021) - O'Neill, Monica C.; Pillai Riddell, Rebecca; Bureau, Jean-François; Deneault, Audrey-Ann; Garfield, Hartley; Greenberg, Saul
Abstract : Abstract: This article consists of 2 separate studies in which the overarching aim was to examine the relationships between caregiver–child behaviours in the vaccination context (infant and preschool) and preschool attachment outcomes. It provides for the first time an examination of acute pain behaviours during early childhood and how it relates to a critical aspect of child development (ie, attachment status) at the end of early childhood. Study 1 examined the longitudinal relationships between caregiver–infant behaviours during infants' first routine vaccination (2 months) and preschool attachment (n = 84). Study 2 examined the concurrent relationships between caregiver–preschooler behaviours during the last routine vaccination of preschool (4-5 years) and preschool attachment (n = 117). Hierarchical multiple regression analyses were used. Although there were several nonsignificant findings, the results revealed that higher caregiver sensitivity and higher proximal soothing 1 minute before the needle during infants' 2-month vaccinations predicted higher levels of preschooler avoidance and lower levels of preschooler ambivalence, respectively. In addition, higher infant pain-related distress at 2 minutes after the needle was related to higher preschooler security and lower preschooler disorganization and controlling-punitive attachments. In terms of concurrent relationships, only caregiver sensitivity was significantly related to preschool attachment outcomes. Specifically, higher caregiver sensitivity at preschoolers' 4- to 5-year vaccinations was related to higher preschooler attachment security. The study findings provide evidence that child–caregiver behavioural patterns during the infant and preschool routine vaccination relate to preschoolers' patterns of attachment. Moreover, it underscores the potential importance of health professionals teaching and supporting attuned caregiving to the child in pain. Abstract : For the first time, caregiver–child pain-related distress and soothing behaviours during infant and preschooler vaccinations are related to a critical distress-regulation outcome (ie, preschool attachment).